Cytotoxic test of different solvents of soursop (Annona muricata) leaf extract against HSC-3 cell line - Areta Vania Bhanuwati; Alfred Pakpahan (Dental Journal, 2022)
Background: Soursop (Annona muricata) leaves have been researched extensively and found to have anticancer properties. The use of soursop as an anticancer treatment is increasingly popular due to its selective cytotoxic activity by acetogenins. The polarity of the extract solvent contributes to the biological activity of the plant, namely cytotoxicity. Purpose: To determine the cytotoxicity of A. muricata leaf extract with ethanol, ethyl acetate and hexane fractions against human oral squamous carcinoma (HSC-3) cell lines. Methods: This experimental laboratory study consisted of twenty four treatment groups tested against the HSC-3 cell line. The ethanol, ethyl acetate and hexane fractions of A. muricata leaves were administered to seven different concentrations, namely 0.3 μg/mL, 3 μg/mL, 25 μg/mL, 50 μg/mL, 100 μg/mL, 150 μg/mL and 300 μg/mL. The control group consisted of three groups: negative control, solvent control and positive control. The percentage of cell viability was calculated by absorbent enzyme-linked immunosorbent assay (ELISA) reader. The cytotoxicity of A. muricata leaf extract against HSC-3 cells was determined by cell counting kit-8 (CCK-8) assay and expressed by IC50 value. The results were analysed using one-way analysis of variance (ANOVA) followed by Tukey’s honestly significant difference (HSD). Results: The results show that the leaf extracts of A. muricata are moderately cytotoxic to HSC-3 cells. The highest cytotoxic activity was found in the ethyl acetate extract with an IC50 value of 76.66 μg/mL – making it the best solvent – then hexane (IC50: 84.14 μg), then ethanol (IC50: 101.32 μg/mL). Statistical analysis using one-way ANOVA and Tukey’s HSD is considered significant p < 0.001. Conclusion: Ethanol, ethyl acetate and hexane fractions of A. muricata leaf extract are moderately cytotoxic, with IC50 values in the range of 21–200 μg/mL.